Unformatted text preview: = ∂ ∂ r r r Thus let, z t x B t x B z & ) , ( ) , ( = r and equation (2) gives y x B B z y x z y x B t E z z & & & & ∂ ∂ − = ∂ ∂ ∂ ∂ ∂ ∂ = × ∇ = ∂ ∂ r r r Coupled Differential Equations for E ± B: x B t E x E t B z y y z ∂ ∂ − = ∂ ∂ ∂ ∂ − = ∂ ∂ xaxis yaxis zaxis E B...
View
Full
Document
This note was uploaded on 05/31/2011 for the course PHY 2061 taught by Professor Fry during the Spring '08 term at University of Florida.
 Spring '08
 FRY
 Physics, Charge, Current, Light

Click to edit the document details